EFEKTIVITAS PENGGUNAAN MEDIA LAGU TERHADAP KEMAMPUAN MENULIS PUISI SISWA KELAS VII SMP NEGERI 35 PADANG - Saswanti, Fini; Nasution, Ismail; Yusandra, Titiek Fujita (Pendidikan Bahasa Indonesia, 2013)
The purpose of this study is as follows. First, describe the learning outcome of students in writing poetry using media track. Second, describe the learning outcome of students in writing poetry without using a media track. Third, comparison of student learning outcomes described in writing poetry with songs and learning to use the media without the media track. Based on the analysis of data and discussion concluded the following. This research is quantitative research with experimental methods. File were obtained through a single type of test, the test performance. Performance tests are used to collect data using the ability to write poetry with songs and media without media track. File is the ability to write poetry using media without media song and compared by using the formula S-gab and continued with the study hypothesis.Based on the analysis file and discussion be conclude as follow. First, the ability to write poetry class VII student at Junior High School 35 Padang using tracks that are in the media more than enough qualifications (74.4) is in the range (66-75). Second, the ability to write poetry without using media song students are qualified enough in (60.9) is in the range (56-65). Third, there are significant differences in learning outcomes in learning to write poetry using media without media song and t-test results on the level of 95% (Î± = 0.05), tcalculated = 3.57 ttable = 1.670 thus H1 is accepted. Effectiveness means that there is the ability to write poetry using the media track. Student learning outcomes in writing poetry with more effective use of the song.